Management of Clavicle Midshaft Fractures: A Comparative Prospective Study in Jammu - Rishabh Gupta; Gagandeep Singh; Amit Kumar (HM Publisher, 2022)
Background: Clavicle fracture, which is also commonly known as a broken collarbone, occurs mostly due to direct high impact energy over the bone due to a fall onto the lateral shoulder or on the outstretched hand. It has been seen that such types of fractures are prevalent among active and sports persons due to sporting activities. This study aimed to assess the pros and cons associated with conservative and surgical management of clavicle fractures. Methods: The present prospective comparative study was conducted at Government Medical College Kathua between February 2021 to January 2022. There was a total of 52 patients, with 26 patients in each group. Group A patients were given conservative management, while Group B patients were operated on for plate fixation. Results: The average fracture union time in group A was slightly higher compared to group B (15.9 vs. 13) weeks. And the difference was statistically significant with a p-value of 0.0483. We observed that there exists a significant difference between the two groups with respect to the total score at 24 weeks (6 months). Evidently, the average CMS score for the conservative group is smaller compared to the operated group (89.95 vs. 94.2) weeks. However, the majority of patients in group A had malaunion complications (65.4%) compared to (3.8%) in group B, and the difference was statistically significant. Conclusion: Evidently, post six months of displaced midshaft clavicle fracture, the rate of complications was more prevalent in group A compared to group B.